Site selective C-H functionalization of Mitragyna alkaloids reveals a molecular switch for tuning opioid receptor signaling efficacy - Bhowmik, Srijita; Galeta, Juraj; Havel, Václav; Nelson, Melissa; Faouzi, Abdelfattah; Bechand, Benjamin; Ansonoff, Mike; Fiala, Tomas; Hunkele, Amanda; Kruegel, Andrew C; Pintar, John E; Majumdar, Susruta; et al. (Nature communications, 2021)
Mitragynine (MG) is the most abundant alkaloid component of the psychoactive plant material "kratom", which according to numerous anecdotal reports shows efficacy in self-medication for pain syndromes, depression, anxiety, and substance use disorders. We have developed a synthetic method for selective functionalization of the unexplored C11 position of the MG scaffold (C6 position in indole numbering) via the use of an indole-ethylene glycol adduct and subsequent iridium-catalyzed borylation. Through this work we discover that C11 represents a key locant for fine-tuning opioid receptor signaling efficacy. 7-Hydroxymitragynine (7OH), the parent compound with low efficacy on par with buprenorphine, is transformed to an even lower efficacy agonist by introducing a fluorine substituent in this position (11-F-7OH), as demonstrated in vitro at both mouse and human mu opioid receptors (mMOR/hMOR) and in vivo in mouse analgesia tests. Low efficacy opioid agonists are of high interest as candidates for generating safer opioid medications with mitigated adverse effects.
Keywords: myši; vazba proteinů; Molecular Structure; Plant Extracts; chemické modely; Protein Binding; Humans; Receptors, Opioid, mu; receptory opiátové mu; lidé; Analgesics; Models, Chemical; rostlinné extrakty; Animals; sekologanin-tryptaminové alkaloidy; Mice; zvířata; Mice, Knockout; ethylenglykol; analgetika; Secologanin Tryptamine Alkaloids; Ethylene Glycol; molekulární struktura; Mitragyna; myši knockoutované